Experimental investigation of shear-extension coupling effect in anisotropic reinforced concrete membrane elements - Kosuru, Ratnasai; Sengupta, Amlan Kumar (Frontiers in Built Environment, 2022)
Performance based analysis under seismic loads using the finite element method for wall-type reinforced concrete (RC) members in buildings and in important structures like liquid retaining structures, nuclear containment structures, offshore concrete gravity structures etc., necessitates the understanding of the non-linear behaviour of the constituent membrane elements. The current orthotropic formulation of the softened membrane model (SMM) can be strictly used only when the reinforcement is symmetric to the principal axes of applied stresses. When the reinforcement is asymmetric, shear strain is generated due to the normal stresses in the principal axes of applied stresses, which is referred to as shear‒extension coupling. An anisotropic formulation is required to capture the generated shear strain. The current study quantifies the shear strain due to asymmetry in reinforcement, by testing panels under biaxial tension-compression using a large-scale panel testing facility. A model for the shear strain is proposed based on the tests data. The paper presents the experimental programme, important test results and the modelling of shear strain. Expression developed for the shear strain can be incorporated in the solution algorithm of the SMM for improved prediction of the shear behaviour of a membrane element. This further aids in accurate prediction of the seismic performance of the important structures mentioned earlier.